2013
DOI: 10.6023/a13030293
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Lithium-Storage Performances of Graphene-Wrapped Cu2+1O/Cu Composites

Abstract: Materials with hybrid metal-semiconductor nanostructures, such as graphene-metal oxides and carbon nanotube-metal oxides, have been intensively exploited as electrode material for lithium ion batteries in recent years. It was found that the structures and properties of the metal-semiconductor herterojunction and the energy level structures of the semiconductor are essential for the conductance of the metal-semiconductor composite. It is thence believed that the conductance, and thus the lithium-storage perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…2,3 By virtue of its extraordinary physicochemical properties, including large surface area, high conductivity, structural exibility and chemical stability, graphene has been intensively explored as an electrode material and/or a substrate of hybrid materials for high performance lithium ion batteries (LIBs). [4][5][6][7][8][9][10][11][12][13][14] It is commonly estimated that graphene might be more suitable for reversible lithium storage than commercial bulk graphite, because the graphene sheets could double the sorption capacity by binding the lithium ion on both sides of the graphene plane and by shortening the lithium diffusion distance. 4,5,[15][16][17][18][19][20] However, it is recently concluded that the lithium coverage on the surface of single layer graphene is actually smaller, because of the lower binding energies of lithium to carbon and the strong Coulombic repulsion of the lithium atoms on the opposite sides of graphene as well as the small charge transfer between lithium and graphene.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 By virtue of its extraordinary physicochemical properties, including large surface area, high conductivity, structural exibility and chemical stability, graphene has been intensively explored as an electrode material and/or a substrate of hybrid materials for high performance lithium ion batteries (LIBs). [4][5][6][7][8][9][10][11][12][13][14] It is commonly estimated that graphene might be more suitable for reversible lithium storage than commercial bulk graphite, because the graphene sheets could double the sorption capacity by binding the lithium ion on both sides of the graphene plane and by shortening the lithium diffusion distance. 4,5,[15][16][17][18][19][20] However, it is recently concluded that the lithium coverage on the surface of single layer graphene is actually smaller, because of the lower binding energies of lithium to carbon and the strong Coulombic repulsion of the lithium atoms on the opposite sides of graphene as well as the small charge transfer between lithium and graphene.…”
Section: Introductionmentioning
confidence: 99%
“…In Fig. 2 23 successfully formed during hydrothermal the process, and Cu foam as 3D conducting scaffold were homogeneously coated by exible graphene sheets. Fig.…”
Section: Characterizationmentioning
confidence: 99%